Ascorbic Acid Facilitates Neural Regeneration After Sciatic Nerve Crush Injury - Li, Lixia; Li, Yuanyuan; Fan, Zhihao; Wang, Xianghai; Li, Zhenlin; Wen, Jinkun; Deng, Junyao; Tan, Dandan; Pan, Mengjie; Hu, Xiaofang; Zhang, Haowen; Lai, Muhua; et al. (Frontiers in Cellular Neuroscience, 2019)
Ascorbic acid (AA) is an essential micronutrient that has been safely used in the clinic for many years. The present study indicates that AA has an unexpected function in facilitating nerve regeneration. Using a mouse model of sciatic nerve crush injury, we found that AA can significantly accelerate axonal regrowth in the early stage (3 days post-injury), a finding that was revealed by immunostaining and Western blotting for antibodies against GAP-43 and SCG10. On day 28 post-injury, histomorphometric assessments demonstrated that AA treatment increased the density, size, and remyelination of regenerated axons in the injured nerve and alleviated myoatrophy in the gastrocnemius. Moreover, the results from various behavioural tests and electrophysiological assays revealed that nerve injury-derived functional defects in motor and sensory behaviour as well as in nerve conduction were significantly attenuated by treatment with AA. The potential mechanisms of AA in nerve regeneration were further explored by investigating the effects of AA on three types of cells involved in this process (neurons, Schwann cells and macrophages) through a series of experiments. Overall, the data illustrated that AA treatment in cultured dorsal root ganglionic neurons resulted in increased neurite growth and lower expression of RhoA, which is an important inhibitory factor in neural regeneration. In Schwann cells, proliferation, phagocytosis, and neurotrophin expression were all enhanced by AA. Meanwhile, AA treatment also improved proliferation, migration, phagocytosis, and anti-inflammatory polarization in macrophages. In conclusion, this study demonstrated that treatment with AA can promote the morphological and functional recovery of injured peripheral nerves and that this effect is potentially due to AA’s bioeffects on neurons, Schwann cells and macrophages, three of most important types of cells involved in nerve injury and regeneration.